Decoupled scenario between the conductive carriers and the ferromagnetism in epitaxial Zn0.85−xMgxCo0.15O thin films - Zhu, Dapeng; Liu Guolei; Tian Yufeng; Shishen, Yan; Cai, Li; Fu Maoxiang; Zhang, Jie; Zhang, Kun; Ye Shengtao; Li Huanhuan; Hu, Shujun; Chen Yanxue; et al. (Applied physics letters, 2014)
A series of Zn0.85−xMgxCo0.15O (0 ≤ x ≤ 0.3) thin films were fabricated by plasma-assisted molecular-beam epitaxy to investigate the correlation between the electrical transport properties and the ferromagnetism. It is observed that the saturation magnetization remains almost unchanged even though the resistivity of the Zn0.85−xMgxCo0.15O films dramatically increases more than 6 orders with increasing Mg concentration. Moreover, the absence of detectable anomalous Hall effects and very small magnetoresistance in the films reveal the absence of spin polarization of conductive carriers and very weak spin-dependent scattering or tunneling processes. All these results suggest that the conductive carriers are decoupled with the ferromagnetism in the Zn0.85−xMgxCo0.15O films.